At Westonci.ca, we make it easy to get the answers you need from a community of informed and experienced contributors. Our Q&A platform provides quick and trustworthy answers to your questions from experienced professionals in different areas of expertise. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Here's the step-by-step process to find the inverse of the given equation \(5y + 4 = (x + 3)^2 + \frac{1}{2}\):
1. Rewrite the equation by interchanging \(x\) and \(y\):
Original equation: \(5y + 4 = (x + 3)^2 + \frac{1}{2}\)
Swap \(x\) and \(y\):
[tex]\[5x + 4 = (y + 3)^2 + \frac{1}{2}\][/tex]
2. Solve for the new \(y\):
- Start by isolating \((y + 3)^2\) on one side of the equation:
[tex]\[5x + 4 - \frac{1}{2} = (y + 3)^2\][/tex]
Combine \(4\) and \(\frac{1}{2}\):
[tex]\[5x + 4 - \frac{1}{2} = (y + 3)^2\][/tex]
[tex]\[5x + \frac{8}{2} - \frac{1}{2} = (y + 3)^2\][/tex]
[tex]\[5x + \frac{7}{2} = (y + 3)^2\][/tex]
- Next, isolate \(y\) by taking the square root of both sides. Remember to include the \( \pm \) symbol as the square root can be both positive and negative:
[tex]\[y + 3 = \pm \sqrt{5x + \frac{7}{2}}\][/tex]
- Solve for \(y\):
[tex]\[y = -3 \pm \sqrt{5x + \frac{7}{2}}\][/tex]
The inverse equation is:
[tex]\[y = -3 \pm \sqrt{5x + \frac{7}{2}}\][/tex]
So, from the given options, the correct inverse equation is:
[tex]\[y = -3 \pm \sqrt{5x + \frac{7}{2}}\][/tex]
Therefore, the right answer is:
[tex]\(y = -3 \pm \sqrt{5x + \frac{7}{2}}\)[/tex]
1. Rewrite the equation by interchanging \(x\) and \(y\):
Original equation: \(5y + 4 = (x + 3)^2 + \frac{1}{2}\)
Swap \(x\) and \(y\):
[tex]\[5x + 4 = (y + 3)^2 + \frac{1}{2}\][/tex]
2. Solve for the new \(y\):
- Start by isolating \((y + 3)^2\) on one side of the equation:
[tex]\[5x + 4 - \frac{1}{2} = (y + 3)^2\][/tex]
Combine \(4\) and \(\frac{1}{2}\):
[tex]\[5x + 4 - \frac{1}{2} = (y + 3)^2\][/tex]
[tex]\[5x + \frac{8}{2} - \frac{1}{2} = (y + 3)^2\][/tex]
[tex]\[5x + \frac{7}{2} = (y + 3)^2\][/tex]
- Next, isolate \(y\) by taking the square root of both sides. Remember to include the \( \pm \) symbol as the square root can be both positive and negative:
[tex]\[y + 3 = \pm \sqrt{5x + \frac{7}{2}}\][/tex]
- Solve for \(y\):
[tex]\[y = -3 \pm \sqrt{5x + \frac{7}{2}}\][/tex]
The inverse equation is:
[tex]\[y = -3 \pm \sqrt{5x + \frac{7}{2}}\][/tex]
So, from the given options, the correct inverse equation is:
[tex]\[y = -3 \pm \sqrt{5x + \frac{7}{2}}\][/tex]
Therefore, the right answer is:
[tex]\(y = -3 \pm \sqrt{5x + \frac{7}{2}}\)[/tex]
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.